THE PHENOMENON OF DISCOURSE IN THE POSTMODERN SOCIETY CULTURE - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article represents the changes of discourse as a social phenomenon in the content of formation of postmodern society. Cultural transformations taking place in various spheres of society life caused the changes of the meaning of discourse.